Statistical methods for analysis of high-throughput RNA interference screens - Birmingham, Amanda; Selfors, Laura M; Forster, Thorsten; Wrobel, David; Kennedy, Caleb J; Shanks, Emma; Santoyo-Lopez, Javier; Dunican, Dara J; Long, Aideen; Kelleher, Dermot; Smith, Queta; Beijersbergen, Roderick L; et al. (Nature methods, 2009)
RNA interference (RNAi) has become a powerful technique for reverse genetics and drug discovery, and in both of these areas large-scale high-throughput RNAi screens are commonly performed. The statistical techniques used to analyze these screens are frequently borrowed directly from small-molecule screening; however, small-molecule and RNAi data characteristics differ in meaningful ways. We examine the similarities and differences between RNAi and small-molecule screens, highlighting particular characteristics of RNAi screen data that must be addressed during analysis. Additionally, we provide guidance on selection of analysis techniques in the context of a sample workflow.